Academic achievement and formal thought in engineering students - Vázquez, Stella Maris (2009)
Introduction: Research on university-level academic performance has significantly linked failure and dropping out to formal reasoning deficiency. We have not found any papers on formal thought in Argentine university students, in spite of the obvious shortcomings ob-served in the classrooms. Thus, the main objective of this paper was exploring the relation between formal operational thought level and academic performance in the 1styear of the en-gineering course.Method. The study was carried out on a sample of 709 first year engineering students from two cohorts of students attending one of four engineering courses during 2006 and 2007 at an Argentine university. Assessment was taken using Tobin and Capie’s (1981) Test of Logical Thinking (TOLT). Data about demographic characteristics and achievement test scores was also collected. Results: Significant relations were observed between formal thought level and student marks in entrance exams, in the partial algebra, calculus, physics and chemistry exams and in the final chemistry exam. Conclusion: This research may be useful as a guide for diagnosis and intervention design, since they point to probabilistic and correlational reasoning as the most difficult skills to de-velop. As the results tend to converge with those of research carried out in other countries, it seems also that the TOLT may be useful in transcultural exploration.